2018
DOI: 10.1107/s2053229617018551
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structure and biological properties of a cis-dichloridobis(diimine)copper(II) complex

Abstract: The mechanisms of interaction of inorganic complexes with DNA are important in the design and development of new metal-based drug molecules. The limitations of cis-platin have encouraged the design and development of new metal-based target-specific anticancer drugs having reduced side effects. The complex cis-dichloridobis(1,2,5-thiadiazolo[3,4-f][1,10]phenanthroline-κN,N)copper(II), [CuCl(CHNS)], has been synthesized and characterized. The complex crystallizes in the monoclinic space group C2/c. The covalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In the present study we found similar result, also when double staining was done to distinguish between live and dead cell significant amount of cell death was observed in cancer cell line treated with ethanolic extract and was comparable with standard drug used as control. DAPI or Double staining showed results which are in accordance with the study done by Bhat et al (2018) (23).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study we found similar result, also when double staining was done to distinguish between live and dead cell significant amount of cell death was observed in cancer cell line treated with ethanolic extract and was comparable with standard drug used as control. DAPI or Double staining showed results which are in accordance with the study done by Bhat et al (2018) (23).…”
Section: Discussionsupporting
confidence: 91%
“…The cytotoxicity of extracted biosurfactant was evaluated on the human lung carcinoma (A549) cell line by [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] (MTT) assay according to the method described by Bhat et al (2018). The absorbance measurements were recorded at 570 nm using a microplate reader.…”
Section: Cytotoxicity Assessmentmentioning
confidence: 99%
“…The cells were incubated with different concentrations of P19 (100, 75, 50, 25, 10, and 2.5 μM) for another 48 h. The cells in each well were washed twice with phosphate buffer solution, and 20 μL of the MTT staining solution (5 mg/ml in phosphate buffer solution) was added to each well, and the plate was incubated at 37 °C. After 4 h, 100 μL of dimethyl sulfoxide (DMSO) was added to each well to dissolve the formazan crystals, and the absorbance at 570 nm was recorded with a microplate reader [63]. Graph Pad Prism Version 5.1 was used to calculate the CC 50 .…”
Section: Cytotoxicity Determination By Mtt Assaymentioning
confidence: 99%